Diagnóstico y propuesta de un manual de control de calidad para la microempresa de ropa deportiva y de trabajo Ecuasport del cantón Shushufindi, provincia de Sucumbíos, para el año 2015 - Villa Suárez, Sandra Alicia (2016)
This project contains a Manual of Quality Control for microenterprise sportswear and working Ecuasport Canton Shushufindi, it has been developed considering that nowadays the demands of consumers as to the quality of products has increased the adoption of a manual of quality control that includes a series of documents such as procedures, instructions, techniques and records, constituting a support tool to achieve customer satisfaction, helping to promote a continuous improvement of the product offering still needed . The proposal made possible to address the various problems encountered, such as the poor quality of the reflected fabric weight and color, resulting in a high percentage of items of second grade, their implementation helps to improve productivity by reducing cost for failures and errors losses. The study was conducted with the use of scientific, inductive, deductive, descriptive statistical methods, and collection of information is the interview conducted by the manager and the survey of 25 workers. From research conducted concludes that microenterprise does not have general standards of quality control, so it was evident that the lack of documented procedures causes ignorance of workers about how to do their job for a quality product, so recommended socialize the general rules set and enforce strict compliance with the quality policy proposal, train staff microenterprise in managing records quality control and make use of the proposed manual, which controls established through all stages of production, ensuring the quality